Fighting terrorism in Africa: benchmarking policy harmonization - Simplice Asongu; Vanessa S. Tchamyou; Jules R. Minkoua N.; Ndemaze Asongu; Nina P. Tchamyou (African Governance and Development Institute (AGDI), 2017)
This study assesses the feasibility of policy harmonization in the fight against terrorism in 53 African countries with data for the period 1980-2012. Four terrorism variables are used, namely: domestic, transnational, unclear and total terrorism dynamics. The empirical evidence is based on absolute beta catch-up and sigma convergence estimation techniques. There is substantial absence of catch-up. The lowest rate of convergence in terrorism is in landlocked countries for regressions pertaining to unclear terrorism (3.43% per annum for 174.9 years) while the highest rate of convergence is in upper-middle-income countries in domestic terrorism regressions (15.33% per annum for 39.13 years). After comparing results from the two estimation techniques, it is apparent that in the contemporary era, countries with low levels of terrorism are not catching-up their counterparts with high levels of terrorism. As a policy implication, whereas some common policies may be feasibly adopted for the fight against terrorism, the findings based on the last periodic phase (2004-2012) are indicative that country-specific policies would better pay-off in the fight against terrorism than blanket common policies. Some suggestions of measures in fighting transnational terrorism have been discussed in the light of an anticipated surge in cross-national terrorism incidences in the coming years.
Keywords: C52; D74; F42; K42; O38; 330; Terrorism; Common policies; Development